IMPACT OF CHILD DOMESTIC LABOUR ON CHILDREN'S EDUCATION. A CASE STUDY OF LUSAKA CITY IN ZAMBIA - Patrick Chanda (European Scientific Journal, ESJ, 2014)
Child labour constitutes a major social problem in Zambia. It not only harms the welfare of individual children, but also slows broader national poverty reduction and development efforts. Children forced out of school and into labour to help their families make ends meet are denied the opportunity to acquire the knowledge and skills needed for gainful future employment, thereby perpetuating the cycle of poverty. This study therefore sought to investigate the impact of child domestic labour on children's education in Lusaka City of Zambia. The study employed an exploratory qualitative case study design. Data collection methods included semi-structured interviews and document analysis. Respondents were purposively sampled for study. Snowball sampling was also used to locate children. The results of the study showed that child domestic labour negatively affects school enrolment as parents send their children to do domestic work to supplement family income. Evidence also showed that for those who attempt to enrol, school attendance becomes poor and eventually they drop out of school to concentrate on work. Moreover, children’s performance at school becomes very poor as they cannot concentrate on their studies and work at the same time. In terms of gender, many girls drop out of school as they are more engaged in domestic work than boys. However, results showed that domestic work enables children to find money to pay school fees and buy school materials. Child-sensitive social protection, free and compulsory education for all children should be the policy measures for elimination of child labour.